IMPACT OF QUALITY AND PRICE ON PURCHASINGDECISION ON FOREIGN CLOTHING COMPANIES AMONGWORKING ADULTS IN KAZAKHSTAN (Journal of Media studies, 2021)
The study aimed to determine the effect of price and quality oncustomers' buying behavior in Kazakhstan who purchases imported brandclothing. The study's goals were to look at variables such as price and qualitythat affect consumer behavior. Furthermore, it has investigated the impact ofconsumer behavior on purchasing choices. By its very nature, this was aqualitative investigation. Simple random selection was used to choose a sampleof 500 working people in Nur-Sultan and Almaty cities for this study, althoughonly 408 took part in the survey as responders. A questionnaire was utilized toobtain data from the study's participants. SPSS was used to analyze the data.Correlation, regression, and SEM were used to verify the hypothesis. Accordingto correlation and multivariate research, both quality and price affect consumerbehavior and purchase decisions in global apparel firms. It also discovered thatconsumer behavior positively correlates with their decision to purchase clothesfrom overseas firms. The report further depicts market decision-making andwhat will drive the fashion industry forward. Overall, the study would aid inunderstanding current consumer preferences in Kazakhstan and estimate thecustomer's future wants, preferences, and expectations trends.